1999
DOI: 10.1086/314963
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Plasma Leptin to Plasma Cytokines and Human Survivalin Sepsis and Septic Shock

Abstract: Leptin production is increased in rodents by administration of endotoxin or cytokines. To investigate whether circulating leptin is related to cytokine release and survival in human sepsis, plasma concentrations of leptin, interleukin (IL)-6, IL-1beta, tumor necrosis factor (TNF)-alpha, soluble TNF receptor type I, IL-1 receptor antagonist (IL-1ra), and the inflammatory modulator IL-10 were measured as soon as severe sepsis (n=28) or septic shock (n=14) developed and every 6 h for 24 h. Patients with sepsis or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
1
11

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(115 citation statements)
references
References 13 publications
8
95
1
11
Order By: Relevance
“…LPS challenge in vivo induced a rapid increase, with peak concentration occurring 3-8 h postchallenge (54,77 ). In reported studies, IL-10 concentrations were increased (22-383 ng/L) in septic adults, whereas it was undetectable in all control and healthy individuals, with the exception in one study (55,58,74,77,83 ). However, IL-10 concentrations are reported to increase within 2 h of blunt trauma, in correlation with injury severity (84 ), and in uninfected surgical patients (83 ), indicating a tendency to participate in the general compensatory antiinflammatory response syndrome.…”
Section: Biomarker Detectionmentioning
confidence: 84%
“…LPS challenge in vivo induced a rapid increase, with peak concentration occurring 3-8 h postchallenge (54,77 ). In reported studies, IL-10 concentrations were increased (22-383 ng/L) in septic adults, whereas it was undetectable in all control and healthy individuals, with the exception in one study (55,58,74,77,83 ). However, IL-10 concentrations are reported to increase within 2 h of blunt trauma, in correlation with injury severity (84 ), and in uninfected surgical patients (83 ), indicating a tendency to participate in the general compensatory antiinflammatory response syndrome.…”
Section: Biomarker Detectionmentioning
confidence: 84%
“…In humans, plasma leptin is elevated in septic patients, and a positive correlation between circulating leptin levels and survival after sepsis has been observed [107][108].…”
Section: Leptin and Acute Inflammationmentioning
confidence: 99%
“…Finally, we did not measure serum VLDL and cholesterol levels to assess whether there was a correlation between the measured parameters and the severity of the disease. Although changes of leptin may be related to changes in total cholesterol, serum triglycerides, and VLDL, it has been demonstrated that leptin is associated with many other systemic diseases such as acute phase response, endotoxemia, sepsis and Eye septic shock 32,33 with no connection to the plasma VLDL and cholesterol status. Indeed, Thong et al 21 studied plasma leptin levels in female athletes to relate it with body fat, nutritional, and endocrine factors, but did not measure plasma lipid status.…”
Section: Discussionmentioning
confidence: 99%